2020
DOI: 10.1007/s10875-020-00851-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunological Characterization of Combined Immunodeficiency Due to TFRC Mutation in Eight Patients

Abstract: Purpose Combined immunodeficiency (CID), due to mutations in TFRC gene that encodes the transferrin receptors (TfR1), is a rare monogenic disorder. In this study, we further characterize the clinical and immunological phenotypes in a cohort of eight patients. Methods A retrospective review of clinical and immunological features of patients diagnosed with a TFRC gene mutation between 2015 and 2019 in three tertiary centers. Results Eight patients from six unrelated families were enrolled. The patients had a med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…102 While common non-coding variants of TFRC have been associated with MCV and RDW, the only known TFRCrelated Mendelian disorder is a homozygous p.Tyr20His (rs863225436, chr3:196,075,339, GenBank: NM_00112 8148.3, c.58T>C, GenBank: NP_001121620.1, p.Tyr20His) substitution reported to cause combined immunodeficiency affecting leukocytes and platelets but not red cells. 103 Common variants of SLC12A7 encoding the potassium ion channel KCC4 have been associated with RDW and other RBC phenotypes. While KCC4 is expressed in erythroblasts, 104 its role in red blood cell function is not well described.…”
Section: Cd36 Tfrc and Slc12a7mentioning
confidence: 99%
“…102 While common non-coding variants of TFRC have been associated with MCV and RDW, the only known TFRCrelated Mendelian disorder is a homozygous p.Tyr20His (rs863225436, chr3:196,075,339, GenBank: NM_00112 8148.3, c.58T>C, GenBank: NP_001121620.1, p.Tyr20His) substitution reported to cause combined immunodeficiency affecting leukocytes and platelets but not red cells. 103 Common variants of SLC12A7 encoding the potassium ion channel KCC4 have been associated with RDW and other RBC phenotypes. While KCC4 is expressed in erythroblasts, 104 its role in red blood cell function is not well described.…”
Section: Cd36 Tfrc and Slc12a7mentioning
confidence: 99%
“…The Transferrin Receptor (CD71) is the primary iron receptor for immune cells and binds to Transferrin (Tf)-bound iron to facilitate internalization of the CD71-transferrin-iron complex. Iron flux and CD71 expression have been shown to be important for T cell activation because missense mutations in the gene for CD71, TFRC , result in combined immunodeficiency (CID) 15 with defective T cell proliferation 16 . Low serum iron conditions can also impede the primary CD8 T cell response to vaccinations 17 and Th1 responses 18 .…”
Section: Introductionmentioning
confidence: 99%
“…In this case, there are TFRC mutations, and the proliferation, function and transformation of T cells and B lymphocytes are affected [30]. A study reported the clinical manifestations and immunological characteristics of 8 patients with TFRC mutations and found T cell function impairment in all patients [31].…”
Section: Discussionmentioning
confidence: 93%